An Applying the Delphi Technique for Eliciting Criteria in Equipment and Materials Used in Highway Construction Projects (Journal of Engineering, 2022)
This article aims to establish and evaluate standards for critical equipment and materials in highway projects in Iraq. Delphi technique has been used to analyze, explore, and discover the main criteria and sub-criteria that affect equipment and materials in highway construction projects in Iraq. To determine the correct response to the criteria presented in this study, a program (IBM, SPSS/V25) was used to assess the main criteria and sub-criteria using the mean score (MS) and standard deviation (SD) technique, as well as to check reliability using Cronbach's alpha factor (α). The experts' qualifications and the extent to which the person is ready to commit are both important factors in panel selection. The design of a questionnaire, which is also identified as questions or repetitions, is based on a clear identification of study objectives, a literature review, and other primary research activities. By applying the Delphi technique steps and procedures, this research reveals fifteen (15) successful criteria in equipment and materials in highway construction projects in Iraq.